2022
DOI: 10.3390/ijerph192114114
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Overall Utility of Measures of Functioning Suitable for School-Aged Children on the Autism Spectrum: A Scoping Review

Abstract: A diagnosis of an autism spectrum condition (autism) provides limited information regarding an individual’s level of functioning, information key in determining support and funding needs. Using the framework introduced by Arksey and O’Malley, this scoping review aimed to identify measures of functioning suitable for school-aged children on the autism spectrum and evaluate their overall utility, including content validity against the International Classification of Functioning, Disability and Health (ICF) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 76 publications
0
9
0
Order By: Relevance
“…ICF-CS can serve as an item pool for developing assessment instruments (Mahdi et al, 2018, Selb, 2015 and guide the researchers in the developing and validating process of new instruments (Bölte et al, 2019). These kinds of measures, resulting from the ICF framework, can improve their clinical utility as they promote more holistic, biopsychosocial, and functional interventions (Hayden-Evans et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICF-CS can serve as an item pool for developing assessment instruments (Mahdi et al, 2018, Selb, 2015 and guide the researchers in the developing and validating process of new instruments (Bölte et al, 2019). These kinds of measures, resulting from the ICF framework, can improve their clinical utility as they promote more holistic, biopsychosocial, and functional interventions (Hayden-Evans et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…One of the clinical applications of the ICF is the linking process of the most commonly used instruments in every health field to ICF categories, and also to specific ICF-CS relevant to neuro-developmental conditions as ASD (D'Arcy et al, 2022;Hayden-Evans et al, 2022). Previous studies have shown the usefulness of this linking process in analyzing measurements used for diagnosing children with ASD such as the Autism Diagnostic Observation Schedule (ADOS-2, Lord et al, 1989) and the Autism Diagnostic Interview (ADI-R, Rutter et al, 2003a) (Castro et al, 2013;Black et al, 2023) as well as the Modified Checklist for Autism in Toddlers (M-CHAT, Robins et al, 2001), the Social Communication Questionnaire (SCQ, Rutter et al, 2003b) the Childhood Autism Rating Scale (CARS, Schopler et al, 2010) (Black et al, 2023) and typical measures of functioning used in the assessment of ASD such as the ABAS-3 (Harrison & Oakland, 2015) or the VINELAND-3 (Sparrow et al, 2005) (Hayden-Evans et al, 2022. This process enables researchers to identify and compare the meaningful units included in different assessment tools with the ICF and provides information about the functional aspects covered by a specific instrument for a health condition (Fayed et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Although standardized measures of functioning (including adaptive behavior) can play a role in identifying challenges underlying support needs [ 16 ], they are unable to extrapolate if the young person and their caregiver places a high value on overcoming these difficulties and if these needs are already being met (and to what degree) by existing supports. Further, functioning and support needs measures frequently span limited domains of functioning (where environmental factors are typically underrepresented) and cannot be tailored to individual life situations [ 43 , 44 , 60 ]. Published reviews critiquing standardized measures of functioning and support needs may be helpful in determining the suitability of the measures for the clinician’s purpose, as well as potential combinations to address all required concepts [ 13 , 43 , 44 , 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Further, functioning and support needs measures frequently span limited domains of functioning (where environmental factors are typically underrepresented) and cannot be tailored to individual life situations [ 43 , 44 , 60 ]. Published reviews critiquing standardized measures of functioning and support needs may be helpful in determining the suitability of the measures for the clinician’s purpose, as well as potential combinations to address all required concepts [ 13 , 43 , 44 , 60 ]. Future research is recommended to develop and validate standardized support needs measures that are aligned with the ICF Core Sets for Autism [ 9 ]; allow active participation from the young person (self-report) and their caregivers (proxy-report); include mechanisms for individualizing the process (for example, through goal setting and other open ended questions); and can draw on existing clinical records (such as assessment of functioning results or progress reports) [ 16 , 20 , 61 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation